A unified framework for developing effective hygiene procedures for hands, environmental surfaces and laundry in healthcare, domestic, food handling and other settings - Bloomfield, Sally F.; Carling, Philip C.; Exner, Martin (German Medical Science GMS Publishing House, 2017)
Hygiene procedures for hands, surfaces and fabrics are central to preventing spread of infection in settings including healthcare, food production, catering, agriculture, public settings, and home and everyday life. They are used in situations including hand hygiene, clinical procedures, decontamination of environmental surfaces, respiratory hygiene, food handling, laundry hygiene, toilet hygiene and so on. Although the principles are common to all, approaches currently used in different settings are inconsistent. A concern is the use of inconsistent terminology which is misleading, especially to people we need to communicate with such as the public or cleaning professionals.This paper reviews the data on current approaches, alongside new insights to developing hygiene procedures. Using this data, we propose a more scientifically-grounded framework for developing procedures that maximize protection against infection, based on consistent principles and terminology, and applicable across all settings.A key feature is use of test models which assess the state of surfaces after treatment rather than product performance alone. This allows procedures that rely on removal of microbes to be compared with those employing chemical or thermal inactivation. This makes it possible to ensure that a consistent "safety target level" is achieved regardless of the type of procedure used, and allows us deliver maximum health benefit whilst ensuring prudent usage of antimicrobial agents, detergents, water and energy.